OBJECT-ORIENTED ONTOLOGY AND NEOLIBERAL CAPITALISM: A MATERIALIST-DISCURSIVE CRITIQUE - CLINCI, Daniel (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Object-Oriented Ontology and Neoliberal Capitalism: A Materialist- Discursive Critique. Object-oriented ontology [OOO], alternatively known as flat ontology or as a branch of speculative realism, has recently been developed and presented as a non-anthropocentric attempt to construct an ontology, a metaphysics, or both. In this paper, I will look at the texts of Graham Harman, probably the most vocal of all the theorists working within the framework of OOO, in order to show that the many flaws of this approach end up legitimizing a neoliberal capitalist worldview and reinforcing its contradictions. Also, one of my goals is to answer a current misunderstanding of object-oriented ontology as posthumanism; OOO is not a posthumanism because it rejects any political discourse and criticism. On the contrary, as we will see, OOO explicitly opposes the new posthumanist materialisms. REZUMAT. Ontologia orientată pe obiect şi capitalismul neoliberal: o critică materialist-discursivă. Ontologia orientată pe obiect [OOO], cunoscută şi drept ontologie plană sau ca ramură a realismului speculativ, a fost dezvoltată şi prezentată recent drept o tentativă non-antropocentrică de a construi o ontologie, o metafizică sau ambele. In acest text, voi analiza textele lui Graham Harman, probabil cel mai vocal dintre teoreticienii care lucrează în cadrul OOO, pentru a arăta că multele probleme ale acestei abordări ajung să legitimeze o perspectivă capitalistă neoliberală şi să îi întărească contradicţiile. De asemenea, unul dintre obiectivele mele este să răspund la o neînţelegere curentă cu privire la ontologia orientată pe obiect drept postumanism; OOO nu este un postumanism deoarece respinge orice discurs politic şi orice critică. Dimpotrivă, după cum vom vedea, OOO se opune explicit noilor materialisme postumaniste. Cuvinte-cheie: ontologie orientată pe obiect, postumanism, noi materialisme, capitalism neoliberal Article history: Received 1 July 2022; Revised 9 September 2022; Accepted 2 October 2022; Available online 27 March 2023; Available print 31 March 2023.